2015
DOI: 10.4103/1319-2442.164562
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes of radial artery wall in patients of chronic kidney disease stage 5 undergoing Av fistula formation and their correlation with serum iPTH levels

Abstract: Vascular complications arise in uremic patients in the absence of clinically significant atherosclerotic disease. Elevated serum parathyroid hormone (PTH) and abnormal calcium (Ca) and phosphorus (P) balance have been implicated in vascular damage in chronic kidney disease (CKD) patients, but there is lack of histo-pathological studies. Patients with CKD stage 5 and 5D who underwent arterio-venous fistula were included in this study. Baseline and laboratory parameters including assessment of total cholesterol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Therefore, the incidence and severity of intimal hyperplasia was higher and greater, respectively, in our work than in Allon's data [ 34 , 36 ]. Tripathi et al [ 38 ] reported that the mean intima thickness of the radial artery was 49.9 mm in 32 Indian ESRD patients, which is similar to our result. However, there was a limitation that the entire circumferential arterial wall could not be acquired during AVF.…”
Section: Effect Of Arterial Pathologic Changes On Early Avf Failuresupporting
confidence: 91%
“…Therefore, the incidence and severity of intimal hyperplasia was higher and greater, respectively, in our work than in Allon's data [ 34 , 36 ]. Tripathi et al [ 38 ] reported that the mean intima thickness of the radial artery was 49.9 mm in 32 Indian ESRD patients, which is similar to our result. However, there was a limitation that the entire circumferential arterial wall could not be acquired during AVF.…”
Section: Effect Of Arterial Pathologic Changes On Early Avf Failuresupporting
confidence: 91%
“…Several variants of some genes were investigated and it was observed that they were related to the EGFR-signaling network and correlated with the activity of oxaliplatin or 5-FU or both in the colon cancer cell lines. It is speculated based on these findings that members of the EGFR-signaling network may be used as potential targets alone or together with oxaliplatin and 5-FU for colon cancer treatment [31]. Moreover; it has been observed that aberrant Wnt signaling pathway is associated with a wide array of tumor types and this pathway plays an important role in the maintenance of stemness of colorectal stem cells [32,33].…”
Section: Molecular Pathwaysmentioning
confidence: 99%